Simulated Problem-Based Learning: Teaching International Law in Exciting Way - Ali, Nik Nor Suhaida (UI Scholars Hub, 2022)
This research aimed to discuss the methods for teaching International Law to non-law students. The subject was offered to second and third-year students of the International Affairs Management program at the School of International Studies, Universiti Utara Malaysia. Since the subject required higher-order thinking skills, it was introduced with Simulated Problem-Based Learning (SPBL), which combines role-playing simulation and problem-based learning (PBL). In western universities, simulations, PBL, and role-playing were popular methods in teaching International Law and International Relations. The methods were shown to improve learning skills but were rarely used in teaching International Law in International Relations programs in Malaysia. Therefore, this study aimed to discuss the application of SPBL in teaching and learning and discuss students’ perception of its implementation. The study used data from the student’s reflective essays. The results showed that this method could help students improve their knowledge and nurture soft communication, confidence, and negotiation skills. Moreover, the students’ prior knowledge class size, duration, and design were vital for the simulations to run smoothly. The SPBL was integral into the International Affairs curriculum because it dealt with current world issues. Therefore, it could be implemented in other courses of the program, though it must be carefully designed and suited to the learning outcomes.